Evaluation of environmental parameters and economic efficiency of integrated farming system on acidic soil and saltwater intrusion in the coastal area: a case study of Mekong Delta, Vietnam - Ha, Vo Van; Di, Huynh Ba; Nha, Duong Van; Phuoc, Nguyen Van (Penerbit Universiti Kebangsaan Malaysia, 2024)
The shift to growing sedge plants, combining raising snails and tilapia in coastal areas could improve the soil nutritional environment, income, and land use efficiency compared to rice monoculture. This study aims to evaluate soil and water environmental factors and to compare the financial efficiency of integrated farming with rice monoculture farming. These experiments were arranged on field land affected by drought and saltwater intrusion in two ecological regions of Kien Giang province. The research found the adaptation of crops (rice, sedge) and aquatic species (snails, tilapia) to the characteristics of acidic and saline soils in coastal areas. The results showed that an integrated farming system reduced soil salinity, but increased soil pH, nitrogen, phosphorus, potassium, and organic matter content more than rice monoculture farming. In addition, this system improved pH, reducing salinity, temperature, and TDS of water more than rice monoculture farming. Acidity and salinity factors affect the rice yield of Winter-Spring crops. The sedge grass (Cyperus malaccensis) grew well under the pH and salinity conditions, but the sedge yield in the dry season was higher than in the rainy season. The weight gain of tilapia (Oreochromis niloticus) was from 0.45 to 0.96 g/day, but fish yield was still low (226 - 541 kg/ha); due to low survival rate (30-36%). Snails (Pila gracilis) adapted well to experimental conditions and the survival rate reached 53-79%. The data analysis of financial efficiency showed that the profit of integrated farming was higher than rice monoculture farming (10,905 to 11,146 USD compared to 904-1,672 USD/ha/year). Therefore, diversified land use in coastal areas to grow sedge grass combined with snails and tilapia increased household income in these study sites.